The education of Augie Merasty : a residential school memoir - Merasty, Joseph Auguste; Carpenter, David, 1941- (University of Regina Press, 2015)
"Now a retired fisherman and trapper, Merasty was one of an estimated 150,000 First Nations, Inuit, and Metis children who were taken from their families and sent to government-funded, church-run schools, where they were subjected to a policy of 'aggressive assimiliation.' As Merasty recounts, these schools did more than attempt to mold children in the ways of white society. They were taught to be ashamed of their Native heritage and, as he experienced, often suffered physical and sexual abuse. Even as he looks back on this painful part of his childhood, Merasty's generous and authentic voice shines through."--Publisher